Self-Efficacy among University of Bisha students (The International Journal of Educational Sciences and Arts, 2025)
This study aimed to assess the level of self-efficacy among students at the University of Bisha and to examine differences in self-efficacy according to gender, academic major, and academic level. A descriptive survey design was employed, and data were collected from a randomly selected sample of 530 male and female students. The instrument utilized was a self-efficacy scale specifically developed by the researcher for university students.Data were analyzed using a one-sample t-test, independent samples t-test, and Mann–Whitney U test. The results indicated a high level of self-efficacy among the participants. Statistically significant differences were observed based on gender, favoring female students. Differences were also significant with respect to academic major, with students in scientific disciplines reporting higher self-efficacy than those in theoretical fields. Furthermore, academic level was a significant factor, with master’s students exhibiting higher self-efficacy than undergraduate students.
Keywords: Self-Efficacy; University Students; University of Bisha